2008
DOI: 10.1159/000156481
|View full text |Cite
|
Sign up to set email alerts
|

Co-Expression of HSV2 and <i>Chlamydia trachomatis</i> in HPV-Positive Cervical Cancer and Cervical Intraepithelial Neoplasia Lesions Is Associated with Aberrations in Key Intracellular Pathways

Abstract: Objective: Oncogenic human papillomaviruses (HPVs) are the etiological agents of cervical cancer. Different cofactors might be needed for malignant transformation, but they still remain elusive. Methods: To delineate the role of Chlamydia trachomatis (CT) and herpes simplex virus type 2 (HSV2) in HPV-positive cervical intraepithelial neoplasia (CIN) lesions and cervical carcinoma a series of 149 cervical cancer and CIN biopsies were analyzed for CT and HSV2 DNA by PCR, and HPV genotyped by InnoLipa. Monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 54 publications
1
56
0
1
Order By: Relevance
“…Like other sexually transmitted genital pathogens, Mycoplasma spp. may be associated with changes in epithelial cells that facilitate entry of HPV virions or with changes in the immunological response pathways that decrease the host’s ability to resolve HPV infection (39, 40). Several bacteria, particularly those capable of establishing persistent infections, can alter host cell cycles, affect apoptotic pathways, and stimulate the production of inflammatory substances linked to DNA damage, thus potentially promote abnormal cell growth (12).…”
Section: Discussionmentioning
confidence: 99%
“…Like other sexually transmitted genital pathogens, Mycoplasma spp. may be associated with changes in epithelial cells that facilitate entry of HPV virions or with changes in the immunological response pathways that decrease the host’s ability to resolve HPV infection (39, 40). Several bacteria, particularly those capable of establishing persistent infections, can alter host cell cycles, affect apoptotic pathways, and stimulate the production of inflammatory substances linked to DNA damage, thus potentially promote abnormal cell growth (12).…”
Section: Discussionmentioning
confidence: 99%
“…Persistent, high-risk HPV infections are more likely to progress to squamous cell carcinoma (SCC) or invasive cervical cancer (ICC) in the presence of identified cofactors including smoking, behavioral factors, age, genetic background and individual immune variation 27. Chronic cervical infection by C. trachomatis has been proposed as a cofactor based on detection of chlamydial DNA in HPV-associated lesions 28 and studies correlating the presence of anti-CT antibodies with risk for ICC or SCC 29. A recent meta analysis of 22 studies (19 retrospective, 3 prospective) determined that C. trachomatis was significantly linked to increased cervical cancer risk prospectively (OR = 2.21, 95% CI: 1.88-2.61, P < 0.001), and retrospectively (OR = 2.19, 95% CI: 1.74-2.74, P < 0.001) 30.…”
Section: Genitourinary Tract Infeciton Disease and Reproductive Sequmentioning
confidence: 99%
“…In addition, we found that women with C. trachomatis have a 2.7 higher chance of presenting multiple infections than a single infection by HPV, although this result was not statistically significant in this sample size (OR, 2.7; 95% CI, 0.8-9.0). Similarly, Paba and colleagues (32) demonstrated that the risk of a woman presenting an infection due to two concomitant types of HPV is 7.2 times higher in the presence of C. trachomatis. One large longitudinal study also showed that prior infection by C. trachomatis is the greatest risk factor for the persistence of HPV DNA (33).…”
Section: Discussionmentioning
confidence: 91%
“…The presence of genital infection is increasingly considered as a risk factor for the persistence of HPV infection and progression of the associated lesions, and the mechanisms of these associations have been the object of various studies (31)(32)(33)(34). In conventional Pap smears, Matheus and colleagues (12) showed a high expression of MMP-9 in the presence of genital infections.…”
Section: Discussionmentioning
confidence: 99%